Beberapa Aplikasi Jaringan Komputer di Indonesia - Abidin, Zainal; Dr. Adnan, Adnan (Biram Samtani Sains, 2024)
Writing this paper aims to determine the aplication of computer networks in Indonesia. The method of writing using the methods of research library. Form the discusion, it can be concluded that some alternative concepts and implementations fo computer networks that exist in Indonesias. Concept / view developed here is not limited to tecnology standpoint but also socio-econimic aspects in particular on the aplication of a technology strategy to a comunity that relies on peoples’s own initiatives independently making it posible to develop Indonesia from below. The world of education and research generally use packet radio technology for operational costs are very cheap, in more detail will be presented several alternative technology that use radio package and reports for the various businesses are currently running, either to make their own aquipment needed such as 1200bps modem, the device is 56Kbps, transverrer and experiment for the relationship to other countries via the polar orbit satelite and satelite geostasionnary. The whore concept developed aiming to rivet the development of a national information system are autonomous and substaninable (sustainable)